The Evaluation of Muhammadiyah Waqf Assets Utilization in Magelang - Fahmi Medias; Eko Kurniasih Pratiwi (IQTISHADIA, 2019)
This article aims to evaluate the utilization of Muhammadiyah waqf assets in Magelang Regency and to analyze the supporting and inhibiting factors in utilizing the assets. This research is expected to become a framework or model for nazhir waqf, which in this case are Muhammadiyah Leaders in Magelang Regency, either from regional/regency level, branch/district level, village, and Muhammadiyah business, in managing and utilizing the waqf assets. The data for this research was collected by in-depth interview, observation on the waqf assets and documentation study, which was then analyzed qualitatively. The result showed that Muhammadiyah leaders of Magelang regency were able to collect waqf assets in form cash of Rp. 156.000.000, - and 415 plots of land spread over 21 sub districts in Magelang regency. The collected assets then were used in developing the field of worship by 20.75%, health by 3.6% and education by 49.55% and social by 26.13%.  The utilization of waqf assets had not been aimed at productive sector in the community’s economy and most of them were led to consumptive sector. It was caused by the lack of socialization of nazhir waqf to the community and the community’s perspective that considers waqf was only in consumptive form.